Photo-double-ionization of ethylene and acetylene near threshold - Gaire, B.; Lee, S. Y.; Haxton, D. J.; Pelz, P. M.; Bocharova, I.; Sturm, F. P.; Gehrken, N.; Honig, M.; Pitzer, M.; Metz, D.; Kim, H.-K.; Schöffler, M.; et al. (My University, 2014)
We present kinematically complete measurements of the photo-double-ionization of ethylene (double CC bond) and acetylene (triple CC bond) hydrocarbons just above the double-ionization threshold. We discuss the results in terms of the coincident kinetic energy of the photoelectrons and the nuclear kinetic-energy release of the recoiling ions. We have incorporated quantum chemistry calculations to interpret which of the electronic states of the dication have been populated and trace the various subsequent fragmentation channels. We suggest pathways that involve the electronic ground and excited states of the precursor ethylene dication and explore the strong influence of the conical intersections between the different electronic states. The nondissociative ionization yield is small in ethylene and high in acetylene when compared with the dissociative ionization channels. The reason for such a striking difference is explained in part on the basis of a propensity rule that influences the population of states in the photo-double-ionization of a centrosymmetric closed-shell molecule by favoring singlet ungerade and triplet gerade final states. This propensity rule and the calculated potential-energy surfaces clarify a picture of the dynamics leading to the observed dication dissociation products.